Using SFL as a Tool for Analyzing Students' Narratives - Doris Correa; Camilo Domínguez (Asociación Colombiana de Profesores de Ingles, 2015)
Traditionally, at universities, English as a foreign language instructors have used a series of approaches to teach students how to write academic texts in English from both teacher preparation and regular programs. In spite of this, students continue to have problems writing the academic texts required of them in the different courses. Concerned with this issue, a group of English as a Foreign Language writing instructors from a Teacher Education Program in Medellín engaged in the study of Systemic Functional Linguistics. The purpose of this article is to report the insights that one of these instructors gained once he began using these theories to analyze a narrative text produced by one of the students in his class.